Effect of active vitamin D on renin in renal tubular epithelial cells under high glucose conditions - Yi-qing He; Wen-wen Liao; Mi Tao; Yu-yan Li; Ping Gao (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the effect of active vitamin D on renin, (pro) renin receptor (PRR) and NF-κB in rat renal tubular epithelial (NRK-52E) cells in high glucose conditions and elucidate the role of NF-κB. Methods NRK-52E cells were cultured in vitro and divided into 7 groups of control, high glucose, high glucose + PDTC (pyrrolidinedithiocarbamate ammonium) and high glucose + 0.1/1/10/100 nM paricalcitol. mRNA and protein expression of renin, PRR and NF-κB p65 in each group were detected by quantitative polymerase chain reaction (qPCR) and Western blot. ChIP-qPCR was utilized for detecting the relationship between NF-κB p65 and the promoter of renin. Results The expressions of renin, PRR and NF-κB spiked in high-glucose group as compared with control group (P<0.05). The expressions of renin and NF-κB declined in high-glucose + PDTC group as compared with high-glucose group (P<0.05). And the expressions of renin, PRR and NF-κB became down-regulated in high-glucose + 100 nM paricalcitol group (P<0.05). ChIP-qPCR demonstrated that NF-κB directly conjugated to the gene promoter region of renin. Conclusion Active vitamin D may reduce high glucose-induced renin expression in renal tubular epithelial cells through an inhibition of NF-κB.